Analisis Perbedaan Produktivitas dan Pendapatan Usahatani Jagung Varietas Bisi-18 dan Varietas Pioner di Kecamatan Jeumpa Kabupaten Bireuen: Rezki Oktian, Teuku Fadhla, M. Nasir Ismail* - Rezki Oktian; Teuku Fadhla; M. Nasir Ismail (Samudra Publisher, 2024)
Corn (Zea mays, Linn) is a food commodity that has been cultivated by Indonesian farmers for a long time. In several areas in Indonesia, corn is also used as a staple food. This study aims to determine and analyze the differences in productivity and income of maize farming of the Bisi-18 variety and the pioneer variety in Jeumpa District, Bireuen Regency. This research method uses a sampling technique that is carried out by stratified random sampling method (random and stratified samples proportionally). The sample size is determined at 20% in each stratum. The results showed that the average production of corn farmers using the Bisi 18 variety was 10,550 kg, with an average farmer income of Rp.26,426,628. While the average production of corn farmers using the Pioner variety is 6,225 kg, with an average farmer income of Rp.14,032,324. The results of the productivity analysis showed that the lowest U value was 36.5, less than the lowest critical U value U(ɑ0.05/2) = 53 and the highest U value was 155.5 greater than the highest U critical value U(ɑ0.05/2) = 139, U values are outside the range of critical U values, so Ho is rejected, Ha is accepted, in other words, accept Ha, reject Ho, which means that the productivity of farmers using the Bisi-18 variety is different from the productivity of farmers using the Pioner variety. The result of income analysis is that the lowest U value is 33, less than the lowest U critical value U(ɑ0.05/2) = 53 and the highest U value is 159 which is greater than the highest U critical value U(ɑ0.05/2) = 139, values - the value of U is outside the range of critical U values, then Ho is rejected, Ha is accepted, in other words accept Ha, reject Ho, which means that the income of farmers who use the Bisi-18 variety is different from the income of farmers who use the Pioner variety.